Genetic Influences on the Amount of Cell Death in the Neural Tube of BXD Mice Exposed to Acute Ethanol at Midgestation. (12th February 2019) - Théberge, Emilie T.; Baker, Jessica A.; Dubose, Candis; Boyle, Julia K.; Balce, Kristina; Goldowitz, Dan; Hamre, Kristin M.
Abstract : Background: Fetal alcohol spectrum disorders (FASD) have a strong genetic component although the genes that underlie this are only beginning to be elucidated. In the present study, one of the most common phenotypes of FASD, cell death within the early developing neural tube, was examined across a genetic reference population in a reverse genetics paradigm with the goal of identifying genetic loci that could influence ethanol (EtOH)‐induced apoptosis in the early developing neural tube. Methods: BXD recombinant inbred mice as well as the parental strains were used to evaluate genetic differences in EtOH‐induced cell death after exposure on embryonic day 9.5. Dams were given either 5.8 g/kg EtOH or isocaloric maltose‐dextrin in 2 doses via intragastric gavage. Embryos were collected 7 hours after the initial exposure and cell death evaluated via TUNEL staining in the brainstem and forebrain. Genetic loci were evaluated using quantitative trait locus (QTL) analysis at GeneNetwork.org. Results: Significant strain differences were observed in the levels of EtOH‐induced cell death that were due to genetic effects and not confounding variables such as differences in developmental maturity or cell death kinetics. Comparisons between the 2 regions of the developing neural tube showed little genetic correlation with the QTL maps exhibiting no overlap. Significant QTLs were found on murine mid‐chromosome 4 and mid‐chromosome 14 only in the brainstem. Within these chromosomal loci, a number of interesting candidate genes were identified that could mediate this differential sensitivity including Nfia (nuclear factor I/A) and Otx2 (orthodenticle homeobox 2). Conclusions: These studies demonstrate that the levels of EtOH‐induced cell death occur in strain‐ and region‐dependent manners. Novel QTLs on mouse Chr4 and Chr14 were identified that modulate the differential sensitivity to EtOH‐induced apoptosis in the embryonic brainstem. The genes underlying these QTLs could identify novel molecular pathways that are critical in this phenotype. Abstract : Fetal alcohol spectrum disorders have a strong genetic component, although the genes that underlie this are currently unknown. We examined a genetic reference population of mice with the goal of identifying genetic loci that could influence ethanol‐induced apoptosis in the early developing neural tube. We found differences in the levels of ethanol‐induced cell death, occurring in strain‐ and region‐dependent manners, and identified candidate genes within significant chromosomal regions that could mediate this differential sensitivity, including Nfia and Otx2 .